2017
DOI: 10.1038/srep45558
|View full text |Cite
|
Sign up to set email alerts
|

Y14 governs p53 expression and modulates DNA damage sensitivity

Abstract: Y14 is a core component of the exon junction complex (EJC), while it also exerts cellular functions independent of the EJC. Depletion of Y14 causes G2/M arrest, DNA damage and apoptosis. Here we show that knockdown of Y14 induces the expression of an alternative spliced isoform of p53, namely p53β, in human cells. Y14, in the context of the EJC, inhibited aberrant exon inclusion during the splicing of p53 pre-mRNA, and thus prevent p53β expression. The anti-cancer agent camptothecin specifically suppressed p53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 26 publications
4
41
0
Order By: Relevance
“…Therefore we examined the expression of a panel of DDR signaling factors in Y14-depleted HeLa cells. Immunoblotting showed that Y14 depletion induced p53β and γH2AX, as previously reported (Lu et al., 2017) and reduced the level of three major upstream DDR kinases, namely, ATM, ATR, and DNA-PK (Figure 2C). A similar result was obtained in Y14-depleted MCF7 and U2OS cells (Figure S4A).…”
Section: Resultssupporting
confidence: 87%
“…Therefore we examined the expression of a panel of DDR signaling factors in Y14-depleted HeLa cells. Immunoblotting showed that Y14 depletion induced p53β and γH2AX, as previously reported (Lu et al., 2017) and reduced the level of three major upstream DDR kinases, namely, ATM, ATR, and DNA-PK (Figure 2C). A similar result was obtained in Y14-depleted MCF7 and U2OS cells (Figure S4A).…”
Section: Resultssupporting
confidence: 87%
“…In contrast to these unique expression events, 12 proteins were significantly altered across all five RXFP3 expression levels (Supplementary Figure 3: PRR14L, SCYL1, CCDC9, NEK7, HIST1H3A, ATPIF1, CDCA2, PAGR1, POTEKP, MTMR1, ZCCHC3, MEPCE). Many of these commonly regulated proteins are known to be associated with energy balance regulation (PRR14L [40]), inflammaging (NEK7 [41]; ATPIF1 [42]), aging associated DNA damage (SCYL1 [43]; CCDC9 [44]; HIST1H3A [45]; ATPIF1 [46]; PAGR1 [47]; ZCCHC3 [48]) or cell senescence (CDCA2 [49]). As such it appears that in addition to expression level effects, a core functionality of the RXFP3 was also evident, which was tightly linked to age-related pathologies.…”
Section: Resultsmentioning
confidence: 99%
“…It is also known to be the core protein of nonsense-mediated mRNA decay (NMD), which monitors abnormal mRNA in eukaryotes [8, 9]. RBM8A is related to RNA transcription, translation, cell cycle regulation and apoptosis regulation [10, 11], and it is also involved in several crucial cell signaling pathways [1215], in which it plays an important role in tumorigenesis and development. Abnormal expression of RBM8A was first detected in cervical cancer [7], and its overexpression was subsequently detected in various malignant tumors, including non-small cell lung cancer and myeloma [1618].…”
Section: Introductionmentioning
confidence: 99%